Unearthing Constraints Experienced by Teacher Unions in Improving the Learning Environment in Schools in Zambia - Sinkala, Henry; Simui, Francis; Muleya, Gistered (Advances in Social Sciences Research Journal, 2022)
The study unearths constraints experienced by teachers' unions in promoting a peaceful learning environment in selected schools of Lusaka, district, Zambia. A case study design was employed on a target population that comprised participants from primary and secondary schools and teacher unions. Expert purposive sampling technique was applied to sample 28 participants from teacher union officials in Lusaka District. Data generated was through interviews and Document Review which was analyzed using themes. Emergent findings revealed that the teachers’ unions faces a myriad of challenges such as inadequate resources, limited knowledge and skills, inaccessible leadership and inadequate financial support in their quest to contribute to a peaceful school environment. Thus, it is recommended among others that, Unions should consider building capacity on resource mobilization and optimal resource utilization, as well as enhancement of mutual consultations with the Ministry of Education and teachers to discuss matters relating to how they can contribute towards raising the standards of learning environment in schools.